Bean production and pest constraints in Latin America - Sanders, J.H.; Schwartz, Howard F. (International Center for Tropical Agriculture, 1980)
Beans are attacked by a large no. of plant pathogens and insect pests, many of which can reduce yields drastically. Farmers with small land holdings usually have limited resources but produce most of the beans in L.A. Control strategies feasible for these growers may be restricted to those strategies that do not require large cash inputs; hence breeding for resistance may be the most desirable alternative available. National and international bean production programs, must accurately identify yield constraints prevalent in specific producton regions to provide more efficient use of the large amount of manpower, research expenditure and time required to implement resistance breeding. Stability of resistant materials can be improved with an integrated control strategy consisting of resistance, cultural practices, chemicals and clean seed production for those diseases in which resistance does not confer immunity to infection. This Integrated control strategy must be adapted to specific regional problems. A more systematic collection of information is necessary to evaluate the costs and probability of success for control strategies so that the pathology, entomology and breeding reseach at the expt station is more applicable and quickly available to farmers. (AS)